IMPROVING THE INSTITUTIONAL SUPPORT FOR THE STATE POLICY OF DEOFFSHORIZATION IN UKRAINE - Feniuk, Yana (Public Management and Policy, 2026)
The article explores the theoretical, methodological, and applied principles of improving the institutional support of the state policy of deoffshorization in Ukraine. The relevance of the problem is substantiated due to the globalization of financial markets, the spread of practices of using offshore jurisdictions, the erosion of the tax base, the reduction of budget revenues and the weakening of the state’s fiscal stability. It is determined that deoffshorization is an important direction of state financial policy, the effectiveness of which depends not only on the quality of regulatory and legal regulation, but also on the institutional capacity of public authorities to ensure coordination, control, information exchange and the implementation of international standards of tax transparency. The paper focuses on the fact that in Ukraine, functions in the field of deoffshorization are distributed between various state institutions; however, the fragmentation of powers, insufficient coordination of actions and the absence of a holistic coordination mechanism reduce the effectiveness of state policy in this area. The article analyzes scientific approaches to understanding deoffshorization through the prism of financial security, tax control, legal regulation, combating tax evasion and the implementation of international standards, in particular the BEPS Action Plan. It is substantiated that the further development of institutional support for deoffshorization should include strengthening interdepartmental cooperation, improving the powers of competent authorities, digitalization of control procedures, increasing the analytical capacity of state institutions and the formation of a comprehensive system for monitoring risks associated with the use of offshore schemes. It is concluded that an effective deoffshorization policy in Ukraine requires a combination of regulatory, organizational, information-analytical and control tools aimed at ensuring financial transparency, strengthening budgetary security and increasing the effectiveness of public administration in the field of counteracting the withdrawal of capital to offshore jurisdictions.